2013
DOI: 10.1111/joms.12028
|View full text |Cite
|
Sign up to set email alerts
|

How Do Developmental and Accommodative HRM Enhance Employee Engagement and Commitment? The Role of Psychological Contract and SOC Strategies

Abstract: In the context of the changing workforce, this study introduced two perspectives on HRM and distinguished universalistic developmental HRM from contingent accommodative HRM. We predicted two separate pathways for the effects on two employee outcomes: work engagement and affective commitment. We expected that developmental HRM would universally relate to employee outcomes by rebalancing the psychological contract between the employee and organization into a less transactional to a more relational contract. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
311
2
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 269 publications
(363 citation statements)
references
References 74 publications
(134 reference statements)
16
311
2
13
Order By: Relevance
“…For each of these practices, respondents were asked to rate their perceptions of these practices in their firms on a five-point Likert scale, ranging from "totally disagreeing" (1) To "totally agree" (5).…”
Section: Methods a Participantmentioning
confidence: 99%
“…For each of these practices, respondents were asked to rate their perceptions of these practices in their firms on a five-point Likert scale, ranging from "totally disagreeing" (1) To "totally agree" (5).…”
Section: Methods a Participantmentioning
confidence: 99%
“…For example, Bal, Kooji, and de Jong (2013) examined how the availability of developmental HRM (including job development/enrichment/rotation, internal promotion, and lateral job movement), at the unit level, was related to engagement, at the individual level, via psychological contract perceptions, at the individual level. The current study complements and extends Bal et al's (2013) study by examining employee perceptions of development practices, rather than just whether they are available to them, and by focusing specifically on opportunities for personal development, rather than on a range of job design/development factors. Focusing on perceptions of HR practices are important as employees vary in how they react to implemented practices, and differ in the attributions they make about why management enact these practices, which influences the way each individual behaves and acts (Nishii, Lepak, & Schneider, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As people experience work-related losses, such as the physical capabilities to conduct work, or the perseverance of working long hours, workplace flexibility may provide older workers the tools to employ SOC-strategies to cope with these losses. Accordingly, a study by Bal et al (2013) indeed found that HRM practices aimed at workplace flexibility, such as reduced working, contributed to higher employee engagement and commitment among workers who were focused on selection and compensation strategies at work. Thus, the SOC-model presents a first indication of how workplace flexibility may contribute to older workers' motivation at work, as the latter facilitates them in adjusting SOC-strategies with how they fulfill their work roles.…”
Section: Selectivity Optimization and Compensation Theorymentioning
confidence: 99%
“…Hence, the SOC-model argues that people use different strategies to cope with the changes they experience as a result of the aging process. The SOCmodel has been used as well to explain changes in people's motivation and goal attainment (Ebner, Freund, & Baltes, 2006;Freund, 2006), as well as how these strategies link to work attitudes and behaviors (Bal, Kooij, & De Jong, 2013;Yeung & Fung, 2009;Zacher & Frese, 2011). Translated to the notion of workplace flexibility, the SOC-model may provide a first indication of why people, as they become older, value more flexibility at work.…”
Section: Selectivity Optimization and Compensation Theorymentioning
confidence: 99%